Phosphorus management in field pea (Pisum sativum) –rice (Oryza sativa) cropping system under temperate conditions - SINGH, S R; NAJAR, G R; SINGH, UMMED (The Indian Journal of Agricultural Sciences, 2012)
A field study conducted during 2005–07 at Sapore, Jammu and Kashmir revealed that application of single super phosphate (SSP) and inoculation of phosphate-solubilizing bacteria (PSB) recorded highest nodulation, yield attributes and yield, net returns, B:C ratio, protein content, N, P uptake and available-soil P than that of DAP and arbuscular mycorrhizal fungi (AMF). Inoculation of PSB increased grain yield (1.70 tonnes/ha) of field pea by 6.92% over AMF (1.59 tonnes/ha). Application of 100% P as basal (M1) being at par with 50% P as basal + 50% P as top dressing (TD) at branching initiation (BI) stage (M3) recorded significantly higher yield attributes, yield, protein content, N, P uptake and available-soil P over 100% P as TD at BI (M2) and 50% P as basal + 25% P as TD at BI + 25% P as TD at before flowering (BF) stage (M4) and enhanced seed yield by 30.4 and 8.4% respectively. Rice grain yield and P uptake was significantly improved with the residual effect of SSP and DAP over control but SSP had significantly higher residual effect over DAP. Inoculation of AMF in field pea showed apparent residual effect over PSB. Method M1 and M3 showed highest direct and residual effect on available-soil P which was 22.5, 19.8, 15.7 and 13.5% higher over M2, respectively.